2018
DOI: 10.2106/jbjs.17.00599
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Tests for Diagnosis of Chronic Periprosthetic Joint Infection Can Help Predict Outcomes of Two-Stage Exchange

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Several studies have been conducted on the management of PJI [10,11] but few provide any data on conservative two-stage revisions and detailed aspects of the type of components that were used for the second stage revision of hip PJI.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the management of PJI [10,11] but few provide any data on conservative two-stage revisions and detailed aspects of the type of components that were used for the second stage revision of hip PJI.…”
Section: Introductionmentioning
confidence: 99%
“…Older age was associated with gram-negative PJI and polymicrobial PJI that had higher failure rates [32, 33]. Recently, Dwyer et al reported higher laboratory tests for diagnosis of PJI could help predict outcomes of two-stage exchange arthroplasty [11]. Additionally, other factors have been identified to associate with treatment failure among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the outcomes are variable with a reported failure rate up to a third of two-stage knee reimplantations [25] and a tenth of two-stage hip reimplantations [3]. Risk factors including the type of organism causing the PJI [26, 27] and preoperative synovial fluid characteristics [28] have been investigated and shown to predict two-stage exchange failures (Table 3). Another factor that has been studied is the timing of reimplantation after the first-stage explant is completed.…”
Section: Discussionmentioning
confidence: 99%